2019
DOI: 10.4274/jtgga.galenos.2018.2018.0027
|View full text |Cite
|
Sign up to set email alerts
|

Association of decreased C1q/tumor necrosis factorrelated protein-5 levels with metabolic and hormonal disturbance in polycystic ovary syndrome

Abstract: Objective: C1q/tumor necrosis factor-related protein-5 (CTRP5) is a novel peptide hormone involved in the metabolism of energy regulation. Polycystic ovary syndrome (PCOS), which is a reproductive and metabolic disorder, is associated with insulin resistance. The aim of the current study was to compare circulating levels of CTRP5 in women with and without PCOS and to investigate possible associations between CTRP5 and metabolic-hormonal parameters. Material and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…75 In the pathogenesis of PCOS, studies have shown a downregulation in adiponectin expression, 76 and lower levels of circulating CTRP3 and CTRP5. 22,23 Conversely, in the present study, we found that high serum levels of CTRP6 inversely correlated with metabolic disturbances in PCOS individuals, when compared with healthy controls, exhibiting a strong independent association with adiponectin. Low levels of adiponectin, CTRP3 and CTRP5 on one hand, and high levels of CTRP6 and CTRP15 on the other, have been witnessed in individuals diagnosed with insulin resistance, metabolic syndrome, and T2DM.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…75 In the pathogenesis of PCOS, studies have shown a downregulation in adiponectin expression, 76 and lower levels of circulating CTRP3 and CTRP5. 22,23 Conversely, in the present study, we found that high serum levels of CTRP6 inversely correlated with metabolic disturbances in PCOS individuals, when compared with healthy controls, exhibiting a strong independent association with adiponectin. Low levels of adiponectin, CTRP3 and CTRP5 on one hand, and high levels of CTRP6 and CTRP15 on the other, have been witnessed in individuals diagnosed with insulin resistance, metabolic syndrome, and T2DM.…”
Section: Discussioncontrasting
confidence: 58%
“…21 Moreover, circulating levels of CTRP3 and CTRP5 were also reported to be reduced in PCOS. 22,23 However, so far, there is no additional evidence on the role of other CTRPs in PCOS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an inverse correlation has been demonstrated between CTRP5 and TG in patients with type 2 diabetes and nonalcoholic fatty liver disease [ 27 ]. Furthermore, a weak negative correlation between CTRP5 and TG and a positive correlation with HDL-C was recently reported in women with polycystic ovary syndrome [ 28 ]. Whereas no correlation between circulating CTRP5 and HDL-C was detected, some shreds of evidence linked the upregulated CTRP5 to increased adipose tissue [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CTRP5 in children's adipocytes was directly correlated to the degree of obesity and their age [ 29 ]. Conversely, several investigations identified an inverse correlation between CTRP5 levels and BMI [ 27 , 28 ]. According to the present data, although BMI was significantly different between RA patients and healthy individuals, we observed a non-significant negative trend between circulating CTRP5 and BMI in RA patients.…”
Section: Discussionmentioning
confidence: 99%